Streptococcus gallolyticus subsp. pasteurianus meningitis complicated by venous sinus thrombosis: A case report. (June 2018) - Wardle, Martin; Mu, Andre; Tong, Steven Y.C.
Highlights: Asplenia is a potential risk factor for Streptococcus gallolyticus meningitis. Cerebral venous sinus thrombosis may complicate S. gallolyticus meningitis. Whole genome sequencing is useful to identify S. gallolyticus subsp. pasteurianus . Abstract: A case of Streptococcus gallolyticus subsp. pasteurianus meningitis, unusually occurring in a splenectomized patient and complicated by cerebral venous thrombosis, is described. Following presentation with meningism and diagnosis and management of S. gallolyticus meningitis, the patient presented again with a further 4 days of fevers and subsequently developed left-sided paresthesias. Cerebral imaging revealed a venous thrombus in the right frontal cortical veins and left sigmoid sinus. The patient recovered following 4 weeks of intravenous ceftriaxone and anticoagulation with enoxaparin and then warfarin. Apart from the splenectomy, no underlying cause was found. The patient was commenced on life-long prophylactic amoxicillin, given appropriate vaccinations, and anticoagulated with warfarin. After initial difficulties, identification of the causative organism to the subspecies level was confirmed by analysis of short-read whole genome sequencing data. This case demonstrates two features that have not previously been reported for S. gallolyticus subsp. pasteurianus infections: splenectomy as a potential risk factor and that infection may be complicated by cerebral venous thrombosis. The resolution provided by whole genome sequencing was valuable in accurately identifying the bacterial subspecies.